Parametric analysis of slotted concrete shear walls reinforced with shape memory alloy bars - Emad Abraik (Elsevier, 2022)
Reinforced concrete (RC) walls are the primary lateral resistance components selected for buildings located in active seismic areas. Special designs and details are typically applied to dissipate energy through inelastic deformation; such a design approach results in significant permanent damage. This study presents a novel slotted RC wall reinforced with superelastic shape memory alloy (SMA) bars within the external components of the slotted RC wall (SMA slotted RC wall). A numerical model was developed and validated by comparing the test results. The seismic performance of the SMA slotted RC wall was numerically investigated using various parameters of interest in seismic applications and evaluated through monotonic and cyclic loading. Compared with other conventional and high-performance RC walls, the proposed SMA slotted RC wall improves load capacity and drift. In addition, the ductility of the proposed system has slightly improved compared to the SMA RC wall. The proposed wall also has an excellent self-centering capability and negligible damage combined with moderate energy dissipation.